The stability of dividends and wages: Effects of competitor inflexibility - Daniel A. Rettl; Alex Stomper; Josef Zechner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We analyze global data about electricity generation and document that the risk exposure of a firm's owners and its workers depends on competitors' ability or willingness to change their output in response to productivity shocks. Competitor inflexibility appears to be a risk factor: the sales of firms with more inflexible competitors respond more strongly to aggregate sales shocks. As a consequence, competitor inflexibility also affects the stability of firms' total wage- and dividend-payments. Firms with relatively flexible competitors appear to smoothen both wages and dividends, but an increase in competitor inflexibility is associated with less dividend-smoothing and more wagesmoothing. Our evidence supports the idea that labor productivity risk associated with competitor inflexibility should be borne by firms' shareholders, rather than by their workers.
urn:nbn:de:hebis:30:3-418687
Keywords: 330